2019
DOI: 10.25182/jgp.2019.14.2.53-60
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of insulin resistance in late adolescent based on anthropometric index

Abstract: The study aimed to evaluate the role of neck circumference for predicting insulin resistance in adolescent compared with waist circumference and waist hip ratio. A cross sectional study was conducted by measuring anthropometric parameters (neck circumference, waist circumference, hip circumference) and biochemical parameter (fasting plasma glucose, fasting insulin, and HOMA-IR) involving 80 late adolescents. Statistical analysis used in this study were Pearson and Spearman correlation, multivariate linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Similarly, increasing waist circumference (Ross et al 2020) and Waist to Hip Circumference Ratio (WHR) could represent abdominal adiposity when compared to BMI (Mulyasari & Pontang 2018). Previous study also found that WC and WHR can be used for predicting insulin resistance in adolescents (Fitriyanti et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, increasing waist circumference (Ross et al 2020) and Waist to Hip Circumference Ratio (WHR) could represent abdominal adiposity when compared to BMI (Mulyasari & Pontang 2018). Previous study also found that WC and WHR can be used for predicting insulin resistance in adolescents (Fitriyanti et al 2019).…”
Section: Introductionmentioning
confidence: 99%